Climate projections of precipitation and temperature in cities from ABC Paulista, in the Metropolitan Region of São Paulo—Brazil - Valverde, María Cleofé; Calado, Bianca Nunes; Calado, Gabrielle Gomes; Kuroki, Larissa Yumi; Brambila, Ricardo; Sousa, Aline Ramos de (Frontiers in Climate, 2023)
Cities are increasingly vulnerable to climate change's impacts and poorly adapted to extreme variability. This study aimed to evaluate climate projections of air temperature and precipitation in seven cities in the Metropolitan Region of São Paulo that correspond to the Greater ABC Paulista. This study uses high-resolution models Eta-HADGEM2_ES (CMIP5), CNRM-CM6-1-HR (CMIP6), and the TerraClimate database to analyze future projections and the specific warming levels (SWLs), respectively. The results show a consensus between the models and the SWLs (2°C and 4°C) for the increase in maximum (Tmax) and minimum (Tmin) temperatures for all municipalities in ABC Paulista in different emission scenarios until the end of the 21st century. For the nearest future (2020-2040), the city of São Caetano do Sul (SCS) shows the highest positive annual anomalies of Tmax concerning the climatological period (1985-2015), for the scenario RCP4.5 (2.8°C) and the RCP8.5 (7.4°C), according to projections from the Eta-HADGEM2_ES, highlighting summer and autumn as the hottest. For precipitation, there was a consensus between the Eta-HADGEM2_ES and the CNRM-CM6-1-HR for a reduction in all scenarios and time-slices 2020-2040 and 2041-2070. The municipalities of Diadema (-78.4%) and SCS (-78%) showed the most significant reductions in December for the RCP8.5, and for SSP5-8.5, SCS shows -30.9% in December for the 2020-2040 time-slice. On the other hand, TerraClimate presents excess rain for Ribeirão Pires (+24.8%) and Santo André (+23.7%) in winter for SWL4. It is concluded that an increase in Tmax and Tmin, as projected, should influence the intensity of extreme heat events in the ABC Paulista region. A reduction in rainfall in its monthly and annual accumulation does not mean a decrease in the extreme daily events that cause floods and landslides in the region. However, it leaves an alert of water scarcity for the supply and demand of the population. ABC Paulista does not have adaptation plans to face extreme climate change. The results should contribute to the first phase of the construction of an adaptation plan, giving a first view of the climate threat that should intensify until the end of the twentieth century affecting the most vulnerable municipalities.